Tuning flat band potential of TiO2 using an electrolyte additive to enhance open circuit voltage and minimize current loss in dye sensitized solar cells. (10th August 2016) - Gondane, Vivekanand; Bhargava, Parag
Graphical abstract: Highlights: We report 8-Hydroxyquinoline(8-HQ) as an alternative electrolyte additive to volatile TBP. 8-HQ resulted in favourable energetic alignment at the TiO2 /dye/electrolyte interface. 8-HQ is effective to minimize the current loss concomitantly enhancement in Voc . 8-HQ is found to be effective partly addressing the Jsc -Voc trade-off problem. Abstract: Electrolyte is an important component of dye sensitised solar cells (DSSC). Its composition, in particular, additives controls the energetic at the TiO2 /dye/electrolyte interface, influencing the performance of dye solar cell. We report here for the first time the use of 8-Hydroxyquinoline (8HQ) as an electrolyte additive to replace costly, volatile 4-tert-butyl pyridine (TBP). Due to its unique structural feature containing hydroxyl and amine group, 8HQ results in remarkable difference in the energy band alignment at the TiO2 /dye/electrolyte interface with respect to that of TBP, as revealed by photocurrent density and Mott-Schottky analysis. Apart from this band shift, 8HQ is very effective in suppressing back electron transfer resulting in enhancement in open circuit voltage. Compared to TBP, additive 8HQ resulted in ∼22% increase in Jsc, with minor loss in Voc (∼5.8%) and 15% increase in photoconversion efficiency with N3 dye. Overall, we found that 8HQ is a highly effective additive in tailoring the TiO2 /dye/electrolyte interface which results in superior performance of dye sensitized solar solar cells as compared to cells with TBP as the additive.